2017
DOI: 10.1111/tesg.12247
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Hydropower in the Communist Space: Iron Gates Revisited

Abstract: This paper proposes a critical discussion of the political economy of hydropower construction in the communist space. We use political economy, economic history and political ecology literature in order to reveal the economic and political relations in which hydropower is embedded in socialist states. The case analysed is the Iron Gates, a joint Romanian‐Yugoslav project which raises specific questions about the techno‐political framework of the new ‘hydraulic landscape’ and its place in socialist economies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…They found that Beijing and Shanghai had the highest level of energy efficiency due to investments, and other parts of China had low energy efficiency by investments. The long-term impact of energy efficiency and sustainability on the population has been revealed by investigating the most significant projects in hydropower energy [48,49].…”
Section: Energy Efficiency Sustainable Economic and Financial Develomentioning
confidence: 99%
“…They found that Beijing and Shanghai had the highest level of energy efficiency due to investments, and other parts of China had low energy efficiency by investments. The long-term impact of energy efficiency and sustainability on the population has been revealed by investigating the most significant projects in hydropower energy [48,49].…”
Section: Energy Efficiency Sustainable Economic and Financial Develomentioning
confidence: 99%
“…The Danube is not only a river that collects the whole inland drainage network of Romania, but also Europe's main navigable waterway, connecting Central Europe to the Black Sea basin, while the Danube-Main-Rhine and the Danube-Black Sea canal system constitute a true transcontinental navigable axis that links Constanţa harbour to the North Sea (Rotterdam). Its particular importance for Romania derives also from the fact that its territory is crossed by the Lower Danube sector (1,075 km, 38% of its total length), basically the most important section in terms of flow and navigation (Creţan, Vesalon, 2017& Văran, Creţan, 2018. Thus, as early as the Middle Ages, the Moldavian and the Wallachian rulers, succeeded in attracting the interest of King Napoleon the Third and of Queen Victoria, who used to call them "Danubian Princes", who supported the unification of all the territories inhabited by Romanians, into a powerful state at the mouths of the Danube, successfully capable of coping with the Russian expansion to the Bosphorus and the Dardaneles (Cazacu, 1999).…”
Section: Romania's Geographical Position and The Elements Defining Itmentioning
confidence: 99%
“…A renewable energy transition in rural areas of low-income countries, where the affordability of electricity provides limited energy availability to its population, could offer an opportunity to mitigate poverty. Nevertheless, in many cases around the world, large energy projects are carried out without paying attention to the potential adverse impacts on poor people [14][15][16]. The provision of clean energy, as Burke [17] suggests, may also provide an improvement not only to basic services, but in job opportunities, additional sources of income, value added to renewable energy sources, and reductions in climate change impacts, among others.…”
Section: Introductionmentioning
confidence: 99%